Perancangan Back-end Api pada Aplikasi Mobile Fruityfit Menggunakan Framework Express JS - Danar Hadi Bachtiar; Paniran Paniran; I Made Budi Suksmadana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Increasing fruit consumption is one of the challenges of public health. To address this, the authors developed a mobile application that allows users to scan and find information related to fruit. FruityFit is an application that can help users to get nutritional and processed information related to certain fruits that can increase users' interest in fruit consumption. This research focuses on constructing the back-end component of the FruityFit application. The design adheres to the REST architectural, leveraging the well-established ExpressJS framework for developmen. To realize the system, we implemented it using a suite of Google Cloud Platform (GCP) services. These services include Cloud Run, App Engine, Cloud Storage, and Cloud SQL, providing a scalable foundation for the back-end infrastructure.. The final result of this research is a REST API that has been running well and documented to help the front-end consume the API.